Development of patatin-like protein purification method from natural rubber industrial waste - Abdullah, Nurul Ain Harmiza; Yusof, Faridah; Mohd Nor, Zairossani (2009)
Skim latex is the byproduct of natural rubber processing. It is treated as effluent and lavishly left in acid pond treatment which creates a lot of environmental problems. The serum extracted from skim latex was found to contain patatin-like protein which is homologous to patatin storage proteins in potato and tomato. Patatin belongs to a group of plant storage glycoproteins that show lipid acyl hydrolase activity which may be a means of defense against plant parasites. A definite method to purify patatin-like protein from rubber waste with minimal loss of target protein is therefore desirable. Three different methods of column chromatography were employed in the purification process to obtain the purified target protein. The success of this protein purification technique was assayed by Sodium dodecyl sulfate-polyacrylamide gel electrophoresis, lipid acyl hydrolase activity analysis and Bradford determination of protein concentration to quantify the protein yield. Through this method, the patatin-like protein from rubber waste was successfully purified. By utilizing this skim latex, most ofthe environmental problems associated with rubber industry could be ruled out and at the same time may turn it into a value-added product. Purification step is crucial in order to minimize time, energy, and cost.